Total syntheses of melodienones by redox isomerization of propargylic alcohols. Issue 23 (25th May 2021) - Dong, Chunmao; Peng, Weiwei; Wang, Huan; Zhang, Xiao; Zhang, Jun; Tan, Guishan; Xu, Kangping; Zou, Zhenxing; Tan, Haibo
Abstract : A remarkable base-promoted methodology for the rapid construction of the ( E )- and ( Z )-γ-oxo-α, β-alkenoic ester skeletons from readily accessible vinyl propargylic alcohols through modified redox isomerization was uncovered. Abstract : A remarkable base-promoted methodology for the rapid construction of the ( E )- and ( Z )-γ-oxo-α, β-alkenoic ester skeletons from readily accessible vinyl propargylic alcohols through modified redox isomerization was uncovered. This approach manifested its high simplicity and efficiency with excellent tolerance of functional substituents, which led to the straightforward structural modifications of various natural products and efficient total syntheses of melodienone, homomelodienone, isomelodienone, and homoisomelodienone within 4 linear steps.